2008
DOI: 10.1128/aem.00704-08
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Distribution of Commensal Fecal Escherichia coli Bacteria in Beef Cattle Administered Selected Subtherapeutic Antimicrobials in a Feedlot Setting

Abstract: Escherichia coli strains isolated from fecal samples were screened to examine changes in phenotypic and genotypic characteristics including antimicrobial susceptibility, clonal type, and carriage of resistance determinants. The goal of this 197-day study was to investigate the influence of administration of chlortetracycline alone (T) or in combination with sulfamethazine (TS) on the development of resistance, dissemination of defined strain types, and prevalence of resistance determinants in feedlot cattle. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 36 publications
1
48
1
1
Order By: Relevance
“…Similar results have been described for fecal samples that have been collected directly from the rectums of feedlot cattle (1,46) and dairy calves (25) that have not been fed AGP. Given the widespread prevalence of tetracycline resistance (40), presumably these cattle were colonized by Tet r bacteria from other environmental sources, most likely prior to their arrival at the feedlot.…”
Section: Discussionsupporting
confidence: 69%
“…Similar results have been described for fecal samples that have been collected directly from the rectums of feedlot cattle (1,46) and dairy calves (25) that have not been fed AGP. Given the widespread prevalence of tetracycline resistance (40), presumably these cattle were colonized by Tet r bacteria from other environmental sources, most likely prior to their arrival at the feedlot.…”
Section: Discussionsupporting
confidence: 69%
“…Actually, tet(A) and/or tet(B), encoding efflux mechanisms, has been reported to be the most common tetracycline resistance determinant in E. coli isolates from humans and animals in many countries (12,13,(20)(21)(22). Previous studies conducted in cattle disagree: some have reported that the tet(A) determinant is dominant in E. coli isolates recovered from cattle (23)(24)(25), whereas others found tet(B) to be dominant (26)(27)(28). In the present study, the prevalences of tet(A) and tet(B) were almost equal at 46.5% and 45.1%, respectively, which is consistent with other reports that showed a similar distribution pattern for the tet gene in E. coli isolates recovered from animals (23,29).…”
Section: Discussionmentioning
confidence: 77%
“…Each animal feeding on an antibiotic becomes a "factory" for the production and subsequent dispersion of antibiotic-resistant bacteria. NTA uses are also clearly linked to the propagation of multidrug resistance (MDR), including resistance against drugs that were never used on the farm (10,52,59,60,92,107,111,132,141,153,154,164). The chronic use of a single antibiotic selects for resistance to multiple structurally unrelated antibiotics via linkage of genes on plasmids and transposons (111,143).…”
Section: Impacts Of Nontherapeutic Usementioning
confidence: 99%